Unintentional transport of fungi propagules to Antarctic biome and the ability to develop at low temperatures - Augustyniuk-Kram, Anna (Studia Ecologiae et Bioethicae, 2020)
Filamentous fungi relatively easily disperse and colonize a variety of substrates, inhabiting various, often extreme environments. Therefore, they spread all over the world. The purpose of the research was to determine whether the propagules of filamentous fungi brought (accidentally transported) into the Antarctic biome by tourists and members of scientific expeditions are capable of developing at low temperatures. In the studies were used seven isolates of fungi: Penicillium sp., Aspergillus flavus, Alternaria alternata, Cladosporium cladosporioides, Trichoderma viride, Geotrichum candidum and Botrytis cinerea. The isolates came from samples collected from tourists and members of scientific expeditions arriving at the Henryk Arctowski Polish Antarctic Station on King George Island in the South Shetland archipelago. Fungal growth was measured at 0, 5, 10, 22°C (as a control) and 10° C, but after having frozen inoculum at -15°C for a period of 7 days. Penicillium sp., Alternaria alternata, Cladosporium cladosporioides, Trichoderma viride, Geotrichum candidum and Botrytis cinerea were found to be capable of growing at low temperatures (5 and 10oC as well as after one freezing cycle, down to -15oC and thawing, up to +10oC). They did not produce a macroscopically visible mycelium at temp. 0oC, however, it was not a lethal temperature for them, as when they were transferred to higher temperatures, they continued to develop even after a fairly long time following the beginning of the experiment. The most vulnerable was Aspergillus flavus. At lower temperatures (from about to 5oC) it did not develop, while freezing and thawing were lethal for this species. Some species (G. candidum, T. viride and B. cinerea), despite the development of mycelium, did not produce spores at lower temperatures.